(untitled) (The Pakistan Development Review, 2012)
Using estimates of schooling demand function and private rate of return to education by gender derived from Household Integrated Economic Survey 2010-11, this paper attempts to examine if there is any dynamics to define a differential behaviour across gender in enrolment in Pakistan and if there is then what can be the possible cause of such discrepancies and how can they be reduced. The first set of analysis focuses on the estimates of probability of enrolment at primary, secondary and tertiary level of education by gender. Strong evidence for higher likelihood of enrolment emerges only at the secondary level of education when the gender is male. The behaviour of the determinants for these schooling demand functions at different levels of education differs by gender. One such key variable is parental education, which is more pronounced in case of mother’s education towards increasing the likelihood of enrolment of girls at the primary and secondary level and of father’s education for boys at all levels and girls at the tertiary level. Hence investing in female education today will not only empower females today but as a positive externality will also lead to gender equity in educational outcomes in the future. Besides this intergenerational externality of investment in female education, the finding establishes that when conditional cash programmes are targeted at mothers as a policy tool they become an effective measure in increasing current female enrolment. Moreover the case for reducing gender disparities in educational outcomes is further supported when we see how gender imbalance in educational attainment and female labour force participation lead to discrepancies in the private rate of return to education by gender. The varied estimates of private rate of returns to education for males and females show that such deviations arise because the females labour force on average is much less educated than males and hence if the object is to raise the rates of returns, a targeted policy for reducing gender differences in enrolment at all levels of education primary, secondary and tertiary will have to be implemented.